2015
DOI: 10.1515/cee-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Static Analysis of the Historical Trusses in Roman Catholic Church of the Holy Kozma and Damian in the Abramová Village

Abstract: This paper treats the stability of two superposed gravitating streams rotating about the axis transverse to the horizontal magnetic field. The critical wave number for instability is found to be affected by rotation for propagation perpendicular to the axis about which the system rotates. The critical wave number for instability is not affected by rotation when waves propagate along the axis of rotation. The critical wave number is affected by both the magnetic field and the streaming velocity in both cases. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Information on proportional and geometric conception may be a guideline for a recovery methodology in relation to the conservation of historic buildings. [8,9] The similar analysis of the truss and its proportional relations in the All Saints Church in Vlčovice in Silesia revealed the similar method "n plus 2" was used to determine the truss height (Figure 7), in the rural house in Vápenná [4,5] as well as in the Trinity Church in Klimkovice (also situated in Silesia) is the use of the similar principle to determine a truss height -the principle of "n plus one". The main difference is in the number of x units within a side of the basic square defining the truss structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on proportional and geometric conception may be a guideline for a recovery methodology in relation to the conservation of historic buildings. [8,9] The similar analysis of the truss and its proportional relations in the All Saints Church in Vlčovice in Silesia revealed the similar method "n plus 2" was used to determine the truss height (Figure 7), in the rural house in Vápenná [4,5] as well as in the Trinity Church in Klimkovice (also situated in Silesia) is the use of the similar principle to determine a truss height -the principle of "n plus one". The main difference is in the number of x units within a side of the basic square defining the truss structure.…”
Section: Resultsmentioning
confidence: 99%
“…This principle has also been identified in other historical roof trusses of Slovakia and Czechia, which we were analysing (eg. roof trusses on a churches in the village of Bela Dulice, Abramova, Okolicne, Klimkovice, Vlčovice and others [3,4,6]). …”
Section: Introductionmentioning
confidence: 99%
“…As in other investigations of trusses, in this case, the principle of the principle "n plus k" was to determine the height of the church depending on its width. For example at the trusses of churches in Dolný Újezd [1], St. Catherine in Banská Štiavnica [14], Klimkovice [15], St. Nicolaus in Podunajské Biskupice [16], St. Cozma and Damianus in Abramova [17] and others [18]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After previous examinations of historical trusses of primarily sacral buildings it was found that one of the most commonly used principles for determining the essentials truss dimensions is a principle we dubbed "n plus one" [4]. It is a principle determining the height of a truss based on its width as follows: the width is divided into 2n units and the height is then (n + 1) units.…”
Section: Geometric Concepts and Proportional Relationships Within Thementioning
confidence: 99%